THE SEMIOTICS ANALYSIS OF VISUAL AND VERBAL SIGNS IN COVID-19 POSTERS OF WHO SEARO FACEBOOK ACCOUNT - Astiti, Ni Made Menuh; Agung, I Gusti Ayu Mahatma (Lexeme : Journal of Linguistics and Applied Linguistics, 2023)
This study aims to find out the sign and also explain the message conveyed by the COVID-19 poster from the Facebook account of World Health Organization South-East Asia Region – WHO SEARO. The source of the data was downloaded from the Facebook account. The researchers used several methods for analyzing the data. There are three theories used in this study. The first one is the theory of meaning by Barthes (in Chandler, 2000) which consists of denotative meaning and connotative meaning. The second theory is the visual aspect and verbal aspect by Dyer (1986) and the last one is the theory of color terms by Wierzbicka (1998). The researchers analyzed two posters from the WHO SEARO Facebook account by using descriptive qualitative method. The result of this study shows that data 1 has 6 visual signs and 5 verbal signs and data 2 consists of 5 visual signs and also 5 verbal signs. Besides visual and verbal signs, the posters also contain the denotative and connotative meanings. In analyzing the connotative meaning, it is also related to the analysis of color term.